Assessment of Heavy Metal Contamination in Wastewater Surrounding the Butwal Industrial Area - Sharma, Krishna Prasad; Pokharel, Bishnu; Subedi, Asish; Neupane, Umesh (Butwal Campus Journal, 2024)
Assessing heavy metal contamination in wastewater is crucial to protect environmental health, as these toxic elements can infiltrate residential areas through groundwater or soil, posing significant risks to human health, ecosystem stability, and the safety of water resources for daily and agricultural use. Quantitative determination of five heavy metals Lead (Pb), Cadmium (Cd), Chromium (Cr), Nickel (Ni) and Zinc (Zn) in six wastewater samples, collected from industries released from Butwal industrial area, was carried out by Atomic Absorption Spectroscopic method. Physicochemical properties pH, conductivity and estimation of chloride concentration were also done by using titrimetric method of analysis. The result showed the wastewater released from industries located in Butwal industrial area is highly contaminated with heavy metals. Lead and Chromium are the most prominent metals found in all wastewater sample above WHO standard limit whereas Nickel, Zinc and Cadmium contamination are within the standard limit.